Detecting strongly lensed supernovae at z [similar to] 5-7 with LSST - Rydberg, Claes-Erik; Whalen, Daniel J.; Maturi, Matteo; Collett, Thomas; Carrasco, Mauricio; Magg, Mattis; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2020)
Supernovae (SNe) could be powerful probes of the properties of stars and galaxies at high redshifts in future surveys. Wide fields and longer exposure times are required to offset diminishing star formation rates and lower fluxes to detect useful number of events at high redshift. In principle, the Large Synoptic Survey Telescope (LSST) could discover large numbers of early SNe because of its wide fields but only at lower redshifts because of its AB mag limit of ∼24. However, gravitational lensing by galaxy clusters and massive galaxies could boost flux from ancient SNe and allow LSST to detect them at earlier times. Here, we calculate detection rates for lensed SNe at z ∼ 5–7 for LSST.
Im Titel wird für "similar to" das Tilde-Zeichen verwendet
Gesehen am 31.03.2020
Advance access publication 2019 November 22